2020
DOI: 10.1080/19490976.2019.1700756
|View full text |Cite
|
Sign up to set email alerts
|

Can gut microbiota of men who have sex with men influence HIV transmission?

Abstract: 2020) Can gut microbiota of men who have sex with men influence HIV transmission?, Gut Microbes, 11:3, 610-619, ABSTRACTGaining a complete understanding of transmission risk factors will assist in efforts to reduce new HIV infections, especially within the disproportionally affected population of men who have sex with men (MSM). We recently reported that the fecal microbiota of MSM elevates immune activation in gnotobiotic mice and enhances HIV infection in vitro over that of fecal microbiota from men who have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…In a prior study we had established that rectal biopsy samples from HIV-positive and negative MSM exhibited higher levels of CCR5 + CD4 + T cells compared to those from non-MSM. 15 To establish whether the gut microbiome is a driver of these differences, we performed in vitro stimulations of LPMCs with FBCs and compared levels of CCR5 + CD4 + T cells across groups. To generate FBCs, whole intact bacteria were isolated from fecal slurries by density gradient centrifugation as described by our group previously.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prior study we had established that rectal biopsy samples from HIV-positive and negative MSM exhibited higher levels of CCR5 + CD4 + T cells compared to those from non-MSM. 15 To establish whether the gut microbiome is a driver of these differences, we performed in vitro stimulations of LPMCs with FBCs and compared levels of CCR5 + CD4 + T cells across groups. To generate FBCs, whole intact bacteria were isolated from fecal slurries by density gradient centrifugation as described by our group previously.…”
Section: Resultsmentioning
confidence: 99%
“… 1 ,2 We had also previously shown that HIV-positive and high-risk MSM had elevated frequencies of the HIV co-receptor CCR5 + on CD4 + T cells in human gut biopsies. 15 Since MSM-associated factors such as trauma, douche, PrEP and antibiotics can also enhance HIV infection and CCR5 expression on CD4 + T cells in MSM, here we performed in vitro experiments specifically designed to examine the effect of the microbiome alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the gut microbiome may increase the risk of contracting HIV ( Coleman et al, 2020 ) via increased expression of integrin and chemokine receptors on T-cells, especially at the level of the colon. Furthermore, it may influence HIV transmission ( Coleman et al, 2020 ), favoring HIV persistence ( Koay et al, 2018 ) through immune activation and systemic inflammation, and impacting the progression from acute HIV infection (AHI; Sortino et al, 2019 ) to AIDS ( Sortino et al, 2019 ), with microbiota diversity correlating with CD4+ T-cell diversity ( Koay et al, 2018 ; Sortino et al, 2019 ). As the disease progresses, an increase in pathogenic species, including Proteobacteria , and a decrease in protective ones (like Bacteroides , Lactobacillus , and Bifidobacterium ) are observed ( Ling et al, 2016 ; Ribeiro et al, 2017 ; Vujkovic-Cvijin et al, 2020 ).…”
Section: The Gut Microbiome and Hiv/aidsmentioning
confidence: 99%
“…To date, MSM-derived gut microbiota have no commonly accepted biomarker that is su ciently robust to accurately predict those MSM with HIV-positive statuses [9,12,13]. Importantly, most studies agree that pathogenic changes in gut microbiota could contribute to HIV progression [8, 9,13,14]. However, the MSM status remains a confounding factor in these analyses, for instance, unprotected receptive anal intercourse, enemas or medication [11].…”
Section: Introductionmentioning
confidence: 99%